Integration of circuit training towards improving shooting ability in athletes of basketball - Muhamad Arifin; Adi Rahadian (Universitas Suryakancana, 2024)
A study was conducted to examine the impact of circuit training on basketball shooting skills among the athletes of Suryakancana University basketball club. The research utilized a experimental design, allowing for a close resemblance to a real experiment. The objective was to test the effect of the independent variable (circuit training) on the dependent variables (shooting skills) and establish a cause- and-effect relationship. The experimental group received the circuit training treatment, while the control group did not. The study involved a population of Suryakancana University basketball club athletes, with a sample size of 20 out of 40 individuals. Results of the research revealed that the 14 week circuit training program had a significant impact on improving shooting skills, as indicated by the N-Gain Score of 0.89, which exceeded the threshold of 0.7. Particularly, the training enhanced arm strength and leg muscle strength among the athletes.